Anesthetic Management in Perioperative Period - Forget, Patrice (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
There are a variety of anesthetic management options during surgery, and these are constantly evolving. Both innovative and confirmatory research are important if the scientific community aims to develop and improve people's quality of care. This reprint introduces new avenues and covers questions regarding innovative anesthetic techniques and unmet needs after surgery, paving the way for future improvements. It can be useful for both clinicians and clinical researchers, especially in light of the expansion of concepts like personalized care.